The parable of the poor widow: in defense of unconscionability in contract law - Núñez del Prado Chaves, Fabio (2024)
The injury in contract law is a notion that has not been exempt from criticisms that question its relevance and usefulness in the Peruvian legal system. In this line, in this paper the author analyzes article 1447 of the Civil Code from different angles, such as the economic analysis of law and diverse national and international doctrine.Finally, the author concludes that this figure is important and necessary for a Rule of Law; but not without first recognizing that the injury in contract law should be rethought, but not eliminated.